Goat’s Milk as a Potential Anti-proliferative against Colon Cancer Cell Lines - Mohd Adzim Khalili, Rohin; Norhayati, Abd. Hadi; Ahmad Zubaidi, A.latif (2021)
Aim: To investigate anti-proliferative effect of fresh and pasteurized goat milk against colon cancer cell lines (HT-29, HCT-116, CT-26). Study Design: Experimental study. Place and Duration of Study: Central Laboratory, Tissue Culture Laboratory, Universiti Sultan Zainal Abidin, Terengganu between January 2020 and April 2020. Methodology: Samples comprised of two types goat milk, which were fresh and pasteurized in powder form. The samples were analysed for the anti-proliferative effect by MTT assay, and IC50 value was determined. Then, cell apoptotic changes were observed by light inverted microscope by 24, 48 and 72 hours. Results: Experimental data showed that the fresh sample produce the highest yield (9.40%) than the pasteurized sample (7.17%). The fresh sample yielded the most potent cytotoxic value (0.28 ± 0.03), followed by pasteurized sample with value IC50 0.32 ± 0.02 against HCT-116 cells. Then, the anti-proliferative effect was observed on cell apoptotic changes by reduction of cell volume, cell densed, and presence of fragmentation and apoptotic bodies at 24, 48 and 72 hours treatment. Conclusion: In conclusion, the fresh sample of goat milk yielded the potent anti-proliferative effect than pasteurized sample